Efficient hydrogenation of concentrated aqueous furfural solutions in to furfuryl alcohol under ambient conditions in presence of PtCo bimetallic catalysts - Dohade, Manisha; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
Furfural (FAL), a major biomass-derived chemical, can be hydrogenated to yield the industrially importantplatform chemical, furfuryl alcohol (FOL). Although heterogeneous catalyst-based methods are known toyield FOL from dilute solutions of FAL, they mainly operate at high temperatures and/or high pressures ofhydrogen and in the presence of organic solvents. In this work, we employ bimetallic PtCo/C catalysts withvarying metal concentrations to achieve the maximum possible FOL yield (100%) at 35 °C under 0.1 MPa H2in water. With concentrated FAL (40 wt%) at 50 °C and under 1 MPa H2pressure, 86% yield of FOL wasobserved. Moreover, eﬃcient catalyst recycling was observed over at least four runs with marginal loss inactivity due to handling error and isolation of FOL in pure form conﬁrmed by NMR and HPLC.Characterization of catalysts with several physico-chemical techniques (XRD, TEM, XPS, ICP, TPR) revealsthe presence of electron-rich Pt and ionic Co species in proximity with each other and these worksynergistically to facilitate maximum possible yield of FOL under ambient conditions and in water medium

Efficient method for cyclopentanone synthesis from furfural: understanding the role of solvents and solubility in a bimetallic catalytic system - Dohade, Manisha; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
The platform chemical, furfural (FAL), is obtained from C5 stream of biomass, and effective conversion into various chemicals including cyclopentanone (CPO) would find many industrial applications. It is desirable to convert FAL to CPO under low H-2 pressure with high selectivity. In the current work, bimetallic catalysts with Pt as the base metal supported on carbon are evaluated in the synthesis of CPO using a biphasic solvent system. By tuning the solvent ratio, with toluene/water (3:4 v/v), 75% yield of CPO is achieved under 1 MPa H-2 at 180 degrees C. The difference in solubility of the substrate, intermediates and products, along with the optimum ratio of Pt and Co metals plays a crucial role in achieving better yields.